2018
DOI: 10.1111/jfpp.13627
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of volatile aroma components from Mantou fermented by different starters

Abstract: This work determines the aroma components in the Mantou fermented by different starters, which were extracted by solid‐phase microextraction and then detected by gas chromatography/mass spectrometry (GC–MS). These volatile components were also measured by electroinc nose. The GC–MS results indicated that 21, 48, 39, 38, 47, and 42 kinds of volatile compounds were detected from Mantou made by Angel low‐sugar high‐activity dry yeast (DY1), Angel high‐sugar‐intolerance high‐activity dry yeast (DY2), high‐activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 39 publications
1
20
0
Order By: Relevance
“…Carboxylic acids showed wax, fat and creamy flavor, which could only be detected in dried noodles fermented for 6 h. Olefins had a high aroma threshold, thus they contributed less to the flavor. Nevertheless, the contents of olefins in fermented steamed breads were always the highest, which was consistent with the results of this study [41]. Additionally, the contents of olefins tended to decrease with the increase of fermentation time.…”
Section: Volatile Compounds In Dried Fermented Noodlessupporting
confidence: 91%
“…Carboxylic acids showed wax, fat and creamy flavor, which could only be detected in dried noodles fermented for 6 h. Olefins had a high aroma threshold, thus they contributed less to the flavor. Nevertheless, the contents of olefins in fermented steamed breads were always the highest, which was consistent with the results of this study [41]. Additionally, the contents of olefins tended to decrease with the increase of fermentation time.…”
Section: Volatile Compounds In Dried Fermented Noodlessupporting
confidence: 91%
“…Naphthalene has a camphoric odor, which is often found in food and aromatic plants. The previous reports showed that naphthalene was a volatile component of steamed bread (Fan et al., 2018), and it was considered to be formed by the thermal degradation of carotenoids (Zepka et al., 2014). In previous literature, benzaldehyde and naphthalene were present in sourdough‐steamed bread, and naphthalene relative peak area was less than 1% (Liu et al., 2018; Wu et al., 2012).…”
Section: Resultsmentioning
confidence: 99%
“…“Jiaozi” starter is used to ferment steamed bread which is called Jiaozi‐steamed breads (JSBs) (Lin et al., 2018). JSBs have more than 1,000 years history and are a traditional staple food with an annual consumption of more than one million tons of wheat flour in China (Zhang et al., 2016), and its unique and pleasant aroma made it widely consumed in northern China (Henan Province, Shanxi Province, Hebei Province, Shandong Province, Shaanxi Province, and Gansu Province) (Fan et al., 2018; Li et al., 2015; Yan et al., 2019). In western world, sourdough is divided into three types (type I, type II, and type III) according to the composition of leavening agents (Pétel et al., 2017; Seitz et al., 1998), and the craftsmanship of Chinese Jiaozi starter is similar to that of European type II sourdough.…”
Section: Introductionmentioning
confidence: 99%
“…3 g of each sample were transferred to and sealed in a 20 mL SPME vial containing 20 μLof internal standard (2-octanol, 14 mg/kg). After the volatile compounds were absorbed by the fiber during a 40 min extraction at 60 ℃ ( Fan et al, 2018 ). Chromatographic separation was achieved using an SH-Rtx-Wax analytical fused silica capillary column (30 m × 0.25 mm × 0.25 μm, Restek Corporation, Benner Circle, Bellefonte, PA, USA), and the column temperature was programmed as follows: the initial temperature was 40 ℃ for 1 min, increased to 160 ℃ at 6 ℃/min, then increased to 250 ℃ at the rate of 3 ℃/min, and then at 250 ℃ for 5 min.…”
Section: Methodsmentioning
confidence: 99%